NILAI PENDIDIKAN DAN SEMANGAT MERAIH CITA-CITA DALAM NOVEL SANG PEMIMPI KARYA ANDREA HIRATA - dinda dinda aulia (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2026)
The purpose of this study is to describe the educational values conveyed by the author in the novel Sang Pemimpi. This research employs a descriptive qualitative method. Based on the results of the study, it can be concluded that through the novel Sang Pemimpi, Andrea Hirata seeks to convey educational values that are highly beneficial for readers through a varied narrative presentation, thereby avoiding a monotonous impression in delivering educational messages. The educational values identified in the novel consist of four types, namely: (a) religious educational values, which reflect a perspective that binds humans to God, the Creator of the universe and all its contents; (b) moral educational values, which serve as a measure of propriety in human behavior within social life; (c) social educational values, which refer to a relatively enduring awareness and emotional attitude toward an object, idea, or person; and (d) cultural educational values, which are related to societal habits and traditions that foster attitudes of hard work and togetherness.